Exploring How Students’ Attitudes Impact Their Performance In English Learning - Frans, Nofry; Wahani, Vera (Indonesian Research Journal on Education, 2025)
This study investigated the relationship between students' attitudes toward learning English and academic achievement. It specifically examined attitudes across cognitive, affective, and behavioral dimensions and English achievement levels. The research utilized an adapted questionnaire based on Abidin, Mohammadi, and Alzwari (2012) to measure students' attitudes, which yielded a high mean score of 3.58. English achievement results were similarly strong, with a mean score of 80.41, indicating excellent performance among students from Sekolah Menengah Atas Universitas Klabat Airmadidi. However, the correlation analysis revealed a coefficient of r = 0.052, rejecting the initial hypothesis. This finding indicates no significant relationship between students' attitudes toward English learning and their academic achievement in English across grade levels XI IPA 1, XI IPA 2, XI IPA 3, and XI IPS at SMA UNKLAB Airmadidi.